Investigate the Different Impacts of Tourism on the Economy and Carbon Emissions of High Income and Middle Income Countries in Asia - Andrasari, Monika; ., Sirojuzilam; Tanjung, Ahmad Albar; Syafii , M. (Journal of Ecohumanism, 2024)
This study investigates the dual impact of tourism on both economic growth and environmental sustainability in high- and middle-income Asian countries. Employing the Seemingly Unrelated Regression (SUR) method, the research analyzes panel data to assess tourism's influence on Gross Domestic Product (GDP) and carbon dioxide (CO2) emissions. The findings reveal that tourism significantly enhances economic growth in high-income countries, whereas its effect on middle-income countries is comparatively modest. Additionally, tourism is found to substantially increase carbon emissions in high-income nations, with a less pronounced impact in middle-income counterparts. These results emphasize the urgent need for developing and implementing holistic, sustainable tourism policies that address both economic and environmental outcomes. While the study offers valuable insights, its scope is limited to Asian countries, which may restrict broader applicability. The originality of this research lies in its integrative approach, advocating for policies that ensure tourism-driven economic growth is both inclusive and environmentally sustainable.